2019
DOI: 10.1186/s13195-019-0482-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a clinical decision support tool on prediction of progression in early-stage dementia: a prospective validation study

Abstract: BackgroundIn clinical practice, it is often difficult to predict which patients with cognitive complaints or impairment will progress or remain stable. We assessed the impact of using a clinical decision support system, the PredictND tool, to predict progression in patients with subjective cognitive decline (SCD) and mild cognitive impairment (MCI) in memory clinics.MethodsIn this prospective multicenter study, we included 429 patients with SCD (n = 230) and MCI (n = 199) (female 54%, age 67 ± 9, MMSE 28 ± 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 48 publications
(81 reference statements)
1
22
0
Order By: Relevance
“…This low efficacy can possibly be explained by the low initial agreement between IPs’ prognosis and the outcome of the decision support tool, which could have influenced IPs’ trust in the tool. Although the percentage of changed prognoses in our study was rather low, this is in line with results from a study on the impact of a decision support tool on prediction of progression in early-stage dementia [ 30 ]. This prospective multicenter study including 429 patients showed that clinicians changed the prediction of progression only in 13% patients after using the tool.…”
Section: Discussionsupporting
confidence: 91%
“…This low efficacy can possibly be explained by the low initial agreement between IPs’ prognosis and the outcome of the decision support tool, which could have influenced IPs’ trust in the tool. Although the percentage of changed prognoses in our study was rather low, this is in line with results from a study on the impact of a decision support tool on prediction of progression in early-stage dementia [ 30 ]. This prospective multicenter study including 429 patients showed that clinicians changed the prediction of progression only in 13% patients after using the tool.…”
Section: Discussionsupporting
confidence: 91%
“…The PredictND (Predict Neurodegenerative Disorders) cohort (PredictND) included patients with MMSE ≥ 25 and contained data from 323 cognitively normal, MCI, and dementia patients from four European memory clinics. The data were acquired during 2015 to 2016 18,19 …”
Section: Methodsmentioning
confidence: 99%
“…There is a need for identifying biomarkers for early detection of AD that can simultaneously predict cognitive trajectories and various AD pathologies, and are specific for AD. Existing predictors based on multi-dimensional data at baseline ( Bruun et al, 2019 , Rhodius-Meester et al, 2018 ) are typically focused on clinical progression of dementia and seem to be limited in linking the cognitive and pathological aspects of AD ( Giorgio et al 2020 ). Although an association has been demonstrated between tau and cognitive impairment ( Bejanin et al, 2017 , Riley et al, 2002 ), studies have largely been correlational and have not fully characterized this connection.…”
Section: Discussionmentioning
confidence: 99%